Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd010988
|View full text |Cite
|
Sign up to set email alerts
|

Sexual counselling for sexual problems in patients with cardiovascular disease

Abstract: Background Sexual problems are common among people with cardiovascular disease. Although clinical guidelines recommend sexual counselling for patients and their partners, there is little evidence on its effectiveness. Objectives To evaluate the effectiveness of sexual counselling interventions (in comparison to usual care) on sexuality-related outcomes in patients with cardiovascular disease and their partners. Search methods We searched CENTRAL, MEDLINE, EMBASE, and three other databases up to 2 March 2015 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
0
16
0
3
Order By: Relevance
“…Several authors reported adequately that assessment of sexual matters is an important factor to prevent loss of sexual activity [23]. Providing patients with sexual health information shows a significant improvement in patients' sexual interest and satisfaction through decreasing patients' and partner level of anxiety and fear from engaging in sexual activities and improve patients' sexual life [22]. It is clear enough that sexual health assessment is an important nursing task [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors reported adequately that assessment of sexual matters is an important factor to prevent loss of sexual activity [23]. Providing patients with sexual health information shows a significant improvement in patients' sexual interest and satisfaction through decreasing patients' and partner level of anxiety and fear from engaging in sexual activities and improve patients' sexual life [22]. It is clear enough that sexual health assessment is an important nursing task [25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CADs are eager to return to their routine after discharge. However, resuming sexual activities is viewed as a challenging activity by patients and their partners [22]. Miner and Kim found that men and their partners have a great concern when they can resume sexual activity safely after CADs [13].…”
Section: Patients' Needs For Sexual Health Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of sexual education for patients will lead to absence or less frequent sexual activity in both male and female patients (Jaarsma et al, 2010). Therefore, providing patients with sexual health information aids in improving patients' sexual interest and satisfaction through decreasing patients' and partner level of anxiety and fear from engaging in sexual activities and improve patients' sexual life (Byrne et al, 2014) Despite supporting evidence and increased attention to sexual health assessment over the years, it is still a challenge for many nurses to address sexual health in practices.…”
Section: Introductionmentioning
confidence: 99%
“…It is still controversial whether the addition of a formal sexual counselling intervention in the context of CR is actually necessary to improve sexual function for these patients. 4 A Cochrane systematic review published in 2016 19 found only 3 trials about this topic. Of these, 1 proposed a highly intensive intervention (eg, 5 hours of sexual therapy provided by a sex therapist) to effectively decrease the time taken to resume sexual activity after a cardiac event, and to improve selfreported sexual function and satisfaction.…”
mentioning
confidence: 99%